Prevalence of Dental Caries among Thermal Power Station Workers in South India - Pillai Dinesh Dhamodhar Mathevan; Sivalingam Balaji; Nyklesh V; Nandini K; Kumarappan Kannan; Nagappan Nagappan (Wolters Kluwer Medknow Publications, 2024)
IntroductionAn increase in the trend of rapid industrialization has resulted in the mushrooming of industries in various sectors throughout the world. This study tries to document caries prevalence among thermal power station workers in South India. Materials and MethodsA pilot study was conducted among 53 thermal power station workers, and based on the same, the sample size was calculated. ResultsThe caries prevalence was 62.5% in thermal power station I workers and 61.5% in thermal power station II workers. The mean DMFT was 2.96 among thermal power station I workers and 2.87 among thermal power station II workers. ConclusionThe caries prevalence was 79.2% in the 35- to 44-year-old age group, according to the National Oral Health Survey and Fluoride Mapping.